Evaluating teaching proficiency among teacher preparation diploma graduates based on InTASC standards - Jehad M. Al-Anati; Diala A. Hamaidi; Yousef M. Arouri (Institute of Advanced Engineering and Science, 2026)
This study aimed to evaluate teaching proficiency of graduates from the higher diploma in teacher preparation program (HDTPP) in Jordan based on the interstate teacher assessment and support consortium (InTASC) standards. To achieve the study objectives, a descriptive quantitative analytical approach was employed. Further, a rating scale was developed covering four domains: learner and learning, content, teaching practices, and professional responsibility. After verifying the validity and reliability of the study instrument, it was distributed to a sample of 686 teachers. The findings revealed that overall teaching proficiency was medium. Further, teaching proficiency across the key domains (learner and learning, content, teaching practice, and professional responsibility) were medium. No statistically significant differences were related to gender. However, there were significant differences related to specialization. Mathematics teachers showed the lowest levels of proficiency. Priorities for improvement were revealed in the “learning differences” standard. The study recommends strengthening teachers’ understanding of individual differences and cultural diversity and applying this knowledge to foster inclusive classrooms. This can be achieved by designing ongoing professional training programs that focus on differentiated teaching strategies and managing diverse learning environments. This will contribute to increasing teaching efficiency and effectively meeting the needs of all learners.